Nitrogen ion beam induced modifications on the properties of carbon quantum dots/TiO2 nanocomposite. (January 2023) - Yashwanth, H.J.; Thorat, A.B.; Dahiwale, S.S.; Dhole, S.D.; Phase, D.M.; Bhoraskar, V.N.; Hareesh, K.
Abstract: The present study reports the modifying the properties of carbon quantum dots/titanium dioxide (CQDs/TiO2, termed as CT) nanocomposite by Nitrogen (N + ) ion beam irradiation in the energy range of 10 keV–40 keV at a fluence of 3 × 10 15 ions cm −2 . Transmission electron microscopic results reveals the anchoring of (3–5) nm CQDs on TiO2 nanoparticles of size ∼25 nm. UV–Visible spectroscopic results show the decrease in the bandgap of CT nanocomposite after N + ion irradiation. X-ray Diffractogram exhibits the shift in the planes of CT nanocomposite due to irradiation. X-ray photoelectron spectroscopic results indicate the presence of nitrogen functional groups after irradiation. Raman spectroscopy results reveal the enhancement in disorder parameters due to irradiation-induced large number of small sp 2 domains of carbon. Photoluminescence spectroscopy results show the decrease in emission intensity of CT nanocomposite after irradiation due to suppression in the recombination rate of photoexcited electron-hole pairs. The work function of CT nanocomposite decreases after ion irradiation indicating the shifting of Fermi energy level towards conduction band as studied by Ultraviolet photoelectron spectroscopy. Photoelectrochemical measurement studies reveals that improvement in the photoelectrochemical performance of 40 keV N + ion irradiated CT compared to TiO2 . Highlights: CQDs/TiO2 nanocomposite is irradiated with 10 keV–40 keV N + ions. 40 keV N + ion irradiated CQDs/TiO2 nanocomposite showed less band gap. The work function was decreased for irradiated CQDs/TiO2 nanocomposite. CQDs/TiO2 irradiated with 40kev N + ions showed six-time higher photocurrent response.